JOB SATISFACTION SEBAGAI PEMEDIASI PENGARUH ORGANIZATIONAL SUPPORT DAN SERVANT LEADERSHIP TERHADAP EMPLOYEE MOTIVATION - Srimulyani, Veronika Agustini (Widya Warta, 2015)
The purpose of this study is to search (1) how the organizational support and servant leadership affect employee motivation and (2) whether job satisfaction acts as a mediating variable. Variables were measuredÂ  using Likert scale technique. The object of the research is 48 operational employees of P.T. Bank Mandiri Madiun. The data analysis made use of hierarchical regression analysis technique with SPSS software version 18. The result of the hypothesis test showed that (1) organizational support and servant leadership had significant positive effect on job satisfaction and employee motivation, (2) job satisfaction had significant positive effect on employee motivation, and (3) job satisfaction acted as perfect or complete mediation on the effect of organizational support toward employee motivation and as a partial mediation on the effect of servant leadership toward employee motivation.